Examining The Correlation and Effect of Quality of Work Life ‎on Job Satisfaction of Bank Employees in Lipa City - Landicho, Bendalyn (International Journal of Accounting and Economics Studies, 2025)
This study assessed the relationship between quality of work life (QWL) and job satisfaction ‎among employees of the Bank in Lipa City. Using a descriptive–correlational design, data were ‎collected from 139 employees selected through stratified proportional random sampling across ‎five BPI branches. Standardized instruments, including Walton’s QWL model and the Job ‎Descriptive Index (JDI), were employed to evaluate employees’ perceptions. Results revealed ‎that employees were generally satisfied with supervision, coworkers, pay, promotional ‎opportunities, and the nature of their work. QWL dimensions such as working conditions, work ‎capacities, opportunities, social relevance, and total life space were rated excellent, while salary ‎and compensation were rated good. Significant relationships were found between QWL and ‎most job satisfaction components, with differences observed based on age and job position but ‎not by sex, civil status, or educational attainment. To strengthen the study’s theoretical ‎contribution, the Human Capital Theory and the Job Demands–Resources (JD–R) Model were ‎incorporated to explain how investments in employee well-being—such as QWL initiatives—‎enhance organizational productivity, financial performance, and long-term sustainability. These ‎frameworks highlight that improving QWL not only drives employee satisfaction but also serves ‎as a strategic economic investment. Based on these findings, tailored human resource ‎interventions, particularly in compensation, training, and support systems, are recommended to ‎enhance both job satisfaction and QWL. A training and development program was also proposed ‎to improve workplace conditions and promote employee well-being‎.